New late silurian to middle devonian acanthodians of the Timan-Pechora region - Valiukevičius, Juozas (2003)
New Pridoli to Eifclian acanthodian scales from various structural units of the Timan-Pechora region are described. Among 15 new species and 1 new genus, there are: 10 new species of nostolepids. common members of most of the biostratigraphic associations, the monospecific genus Monosp'ma gen. nov., a single new species of Chdracanthoides (all Climatiida), Diplacanthus pechorensis sp. nov. (Diplacanthida), and two new species of Gomphunchus (Ischnacanthida). Besides morphologic descriptions the taxa are also characterised histologically. Acanthodian taxa with scale crowns and bases composed of cellular bone, or very similar tissue, proposed as a primitive feature in their evolution, are reported for the first time.